2009
DOI: 10.1063/1.3274675
|View full text |Cite
|
Sign up to set email alerts
|

Simple and efficient scanning tunneling luminescence detection at low-temperature

Abstract: We have designed and built an optical system to collect light that is generated in the tunneling region of a low-temperature scanning tunneling microscope. The optical system consists of an in situ lens placed approximately 1.5 cm from the tunneling region and an ex situ optical lens system to analyze the emitted light, for instance, by directing the light into a spectrometer. As a demonstration, we measured tip induced photoluminescence spectra of a gold surface. Furthermore, we demonstrate that we can simult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…In this paper we have demonstrated that the radiative modes of a plasmonic nanocavity can be studied by a combination of STML and STS through a novel procedure that eliminates all the electronic-structure contributions to the measured far-field optical spectra. The method is based on the relationship between the rate of inelastic tunnelling events with energy loss ℎ at a bias voltage and the total tunnel current at a lower bias To collect the emitted light we modified the head of our STM following the procedure described in [37]. Our light detection set-up is formed by three lenses, one in UHV and two in air, three mirrors, and an optical spectrometer (Andor Shamrock 500) equipped with a Peltier Discussion on the normalization process…”
Section: Discussionmentioning
confidence: 99%
“…In this paper we have demonstrated that the radiative modes of a plasmonic nanocavity can be studied by a combination of STML and STS through a novel procedure that eliminates all the electronic-structure contributions to the measured far-field optical spectra. The method is based on the relationship between the rate of inelastic tunnelling events with energy loss ℎ at a bias voltage and the total tunnel current at a lower bias To collect the emitted light we modified the head of our STM following the procedure described in [37]. Our light detection set-up is formed by three lenses, one in UHV and two in air, three mirrors, and an optical spectrometer (Andor Shamrock 500) equipped with a Peltier Discussion on the normalization process…”
Section: Discussionmentioning
confidence: 99%
“…The experiments were performed with an Omicron STM operating at 4.6 K in ultrahigh vacuum. The setup was adapted to light emission measurements following the design developed in [19]. In this setup a lens (fnumber = 1.5) is fixed to the STM head so that the tip-sample junction can be precisely located at the lens focal point.…”
mentioning
confidence: 99%
“…1(b), it can already be seen by the dark rims around islands and substrate steps that the photon emission is significantly reduced when the STM tip is placed near a step edge. Such a reduced intensity at step edges has already been observed on other closely packed noble metal surfaces like Au(111) [22], Au(110) [23], Cu(111) [24], and Ag(111) [4,25,26], whereas on Au(110), enhanced emission was observed at step edges [5,27]. The effect was finally attributed by Hoffmann et al [5] to the local density of states (LDOS) at the step edge.…”
Section: A Step-edge Effectmentioning
confidence: 72%